1997
DOI: 10.2105/ajph.87.6.1027
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of patient reading ability to self-reported health and use of health services.

Abstract: OBJECTIVES: This study examined the relationship of functional health literacy to self-reported health and use of health services. METHODS: Patients presenting to two large, urban public hospitals in Atlanta, Ga, and Torrance, Calif, were administered a health literacy test about their overall health and use of health care services during the 3 months preceding their visit. RESULTS: Patients with inadequate functional health literacy were more likely than patients with adequate literacy to report their health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
446
3
12

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 610 publications
(482 citation statements)
references
References 23 publications
21
446
3
12
Order By: Relevance
“…Those with poor health literacy are at higher risk for seeking emergency care, have more frequent hospital admissions with longer stays in the hospital [21], are prone to missing medical appointments, have poor compliance with treatment recommendations [1,5,18,39,44,51], and greater disease progression [28]. Patients typically have reading skills that are about five grades lower than the highest attained educational grade [26,31].…”
Section: Where Are We Now? the Patient And Societymentioning
confidence: 99%
See 1 more Smart Citation
“…Those with poor health literacy are at higher risk for seeking emergency care, have more frequent hospital admissions with longer stays in the hospital [21], are prone to missing medical appointments, have poor compliance with treatment recommendations [1,5,18,39,44,51], and greater disease progression [28]. Patients typically have reading skills that are about five grades lower than the highest attained educational grade [26,31].…”
Section: Where Are We Now? the Patient And Societymentioning
confidence: 99%
“…An individual's health literacy is considered the single best predictor of their health status [5,27,51]. Health literacy is defined as the ''capacity to obtain, interpret, and understand basic health information and services and the competence to use such information and services to enhance health'' [22,44].…”
Section: Introductionmentioning
confidence: 99%
“…2 Early on, this led many researchers and health professionals to design solutions to the problem that solely involved the modification of health materials following best practices for plain language and format. 3,4 Consequently. these interventions were somewhat effective at improving comprehension and knowledge, but had variable to no impact on behavior.…”
Section: Introductionmentioning
confidence: 97%
“…Studies have shown that persons with less education and lower health literacy are less likely to undergo routine cancer screening, and more likely to be uninsured or of low income (7)(8)(9). Women who live in economically deprived areas of the United States and Great Britain have been reported to have an increased mortality and other poor health outcomes (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%